Iron encapsulated carbon nanotube composites embedded in alumina with enhanced magnetic properties. (February 2022) - Rhodes, Steven; Cribb, Warner; Taufour, Valentin; Patterson, Dwight; Seifu, Dereje; Kamali, Saeed; Neupane, Suman
Abstract: Alumina is an essential ceramic insulator, while carbon nanotubes (CNTs) have intriguing mechanical, thermal, electrical, and magnetic properties. We report on the synthesis of CNTs/Al2 O3 nanocomposites using the chemical vapor deposition (CVD) process using iron as a catalyst. The as-prepared composite's structure and morphology are characterized by transmission electron microscope, scanning electron microscope, X-ray diffractometer, thermogravimetric analyzer, and Mössbauer spectroscopy. The experimental results show that these composites contain CNTs of an average diameter of 40 nm distributed homogenously within the alumina matrix. The percentage of CNTs within the composites is at 7%. The CNT/Al2 O3 nanocomposites demonstrate a dramatic enhancement of ferromagnetic properties during vibrating sample magnetization measurements. As compared to the magnetization of 0.03 e.m.u./g at an applied field of 1.5 T for the Fe-catalyzed Al2 O3, the saturation magnetization of CNT/Al2 O3 is 1.78 e.m.u./g, which represents an increment of ∼5800%. The coercivity of CNTs/Al2 O3 composites increased from 0.036 T at 300 K to 0.285 T at 5 K. This study provides a relatively simple approach to blending the magnetic properties with potential thermoelectric materials. Highlights: Carbon nanotube/alumina nanocomposites synthesized by one-step chemical vapor deposition process. The saturation magnetization of the composites represents 5800% increment as compared to the starting material. The composites demonstrated significant magnetic "hardening" under cryogenic conditions due to frozen magnetic moments.